SMART TRACER: APLIKASI MONITORING BERKAS REKAM MEDIS BERBASIS WEB - Denos Imam Fratama; Imrah Sari; Herman Susilo; Andri Swandi; Dede Fauzi (Ensiklopedia Research and Community Service Review, 2026)
Hospital medical record management continues to encounter numerous operational challenges, including difficulty in locating files, delays in returning documents, inaccurate manual entries, and the potential for misplacement or permanent loss of records. Smart Tracer is a web-based solution developed to enable digital, real-time monitoring of medical record file circulation. This study was conducted to design and build a web-based monitoring system for medical record documents employing the Waterfall software development methodology. Functional verification was performed through Black Box Testing to confirm that each system component operates correctly. The findings demonstrate that Smart Tracer delivers eight integrated capabilities: user authentication, medical record data administration, borrowing and return transaction recording, real-time document status and location tracking, rapid file retrieval, circulation history logging, an interactive monitoring dashboard, and automated activity reporting. Each tested function yielded valid outcomes that met the defined system specifications. Smart Tracer is intended to enhance the overall effectiveness of medical record administration, streamline document tracking workflows, and advance digital transformation in health information management.Keywords: Medical Record, Monitoring System, Web-Based Application, Waterfall Method, Black Box Testing